Pengembangan Desain Pembelajaran Model Addie dengan Teknik Jigsaw pada Siswa Kelas 5 SD Negeri Empang Bahagia 3 Kota Tangerang - Magdalena, Ina; Fazriah, Nurul; Nahzifa, Nanda (YASIN, 2023)
The learning process in the development of science and technology increasingly encourages reform efforts in the use of technological results to improve student achievement. The use of learning media is expected to help students understand and accept the learning process carried out by the teacher. In the process of selecting teacher methods, media and materials must be based on three levels of student ability and learning objectives, namely choosing the right method so that the teacher can attract and interest students during the teaching and learning process. The purpose of this study is to develop the ADDIE Model learning design for 5th grade students at SD Negeri Empang Bahagia 3, Tangerang City. The method used is the ADDIE model which has 5 phases, the first is Analysis, Design, Development, Implementation and Evaluation. The result of this study is that the development of the ADDIE model is comprehensive and systematic. The teachers succeeded in producing teaching materials that emphasized the three main components of the active learning method, namely Jigsaw, Video Shows, Assessment Assignments.